The effect of diclofenac mouthwash on periodontal postoperative pain - Jaber Yaghini; Ahmad Moghareh Abed; Seyed Abolfazl Mostafavi; Najmeh Roshanzamir (Dental Research Journal, 2011)
Background: The need to relieve pain and inflammation after periodontal surgery and the side effects of systemic drugs and advantages of topical drugs, made us to evaluate the effect of Diclofenac mouthwash on periodontal postoperative pain. Methods: In this double-blind, randomized clinical trial study 20 quadrants of 10 patients(n = 20) aged between 22-54 who also acted as their own controls, were treated using Modified Widman Flap procedure in two quadrants of the same jaw with one month interval between the operations. After the operation in addition to ibuprofen 400 mg, one quadrant randomly received Diclofenac mouthwash (0/01%) for 30 seconds, 4 times a day (for a week) and for the contrary quadrant, ibuprofen and placebo mouthwash was given to be used in the same manner. The patients scored the number of ibuprofen consumption and their pain intensity based on VAS index in a questionnaire in days 1, 2, 3 and the first week after operation. The findings were analysed using two-way ANOVA, t-test and Wilcoxon. P-value less than 0.05 considered to be significant. Results: There was a significant difference between the mean values of pain intensity of two quadrants in four periods (P = 0.031). But, there was no significant difference between the average ibuprofen consumption in two groups (P = 0.51). Postoperative satisfaction was not significantly different in two quadrants (P = 0.059). 60% of patients preferred Diclofenac mouthwash. Conclusion: Diclofenac mouthwash was effective in reducing postoperative periodontal pain but it seems that it isn′t enough to control postoperative pain on its own.